Reducing corruption and developing public services in Bangladesh through e-government - Habib Khan, Md. Noman; Kabbashi, Nassereldeen Ahmed (2013)
Many developing countries are actually desiderating to decorate their country. To do so, they need e-Government which is helping them to provide their focused, cost effective and easy to solve their problems. Moreover, people can share their problems and needs flatly. Bangladesh is a country where, notwithstanding political lubricity and other different problems, e- Government is the compatible decision. This study solves many questions which is actually difficult to solve by other technique. E-Government virtually related with two things. First one is flourishing government–citizen relationships and the next one is reducing corruption. The results of using this technique are immense. As e-Government improves the public services, it’s actually helpful to deduct the corruptions and improve the relationship between government and public.